Citicoline Protects Auditory Hair Cells Against Neomycin-Induced Damage - Zhong, Zhenhua; Fu, Xiaolong; Li, He; Chen, Jie; Wang, Maohua; Gao, Song; Zhang, Liyan; Cheng, Cheng; Zhang, Yuan; Li, Peipei; Zhang, Shasha; Qian, Xiaoyun; et al. (Frontiers in Cell and Developmental Biology, 2020)
Aminoglycoside-induced hair cell (HC) loss is one of the most important causes of hearing loss. After entering the inner ear, aminoglycosides induce the production of high levels of reactive oxygen species (ROS) that subsequently activate apoptosis in HCs. Citicoline, a nucleoside derivative, plays a therapeutic role in central nervous system injury and in neurodegenerative disease models, including addictive disorders, stroke, head trauma, and cognitive impairment in the elderly, and has been widely used in the clinic as an FDA approved drug. However, its effect on auditory HCs remains unknown. Here, we used HC-like HEI-OC-1 cells and whole organ explant cultured mouse cochleae to explore the effect of citicoline on aminoglycoside-induced HC damage. Consistent with previous reports, both ROS levels and apoptosis were significantly increased in neomycin-induced cochlear HCs and HEI-OC-1 cells compared to undamaged controls. Interestingly, we found that co-treatment with citicoline significantly protected against neomycin-induced HC loss in both HEI-OC-1 cells and whole organ explant cultured cochleae. Furthermore, we demonstrated that citicoline could significantly reduce neomycin-induced mitochondrial dysfunction and inhibit neomycin-induced ROS accumulation and subsequent apoptosis. Thus, we conclude that citicoline can protect against neomycin-induced HC loss by inhibiting ROS aggregation and thus preventing apoptosis in HCs, and this suggests that citicoline might serve as a potential therapeutic drug in the clinic to protect HCs.